Development of a library for clients of ONVIF video cameras: challenges and solutions - Lopes, Sérgio F. (2013)
The interoperability of IP video equipment is a critical problem for surveillance systems and other video application developers. ONVIF is one of the two specifications addressing the standardization of networked devices interface, and it is based on SOAP. This paper addresses the development of an ONVIF library to develop clients of video cameras. We address the choice of a web services toolkit, and how to use the selected toolkit to develop a basic library. From that, we discuss the implementation of features that ...